The essence of the modern treatment of schizophrenia - Delgado, Honorio (1940)
They can be considered modern curative procedures of schizophrenia: the pyrotherapy, prolonged narcosis, convulsive seizures induced with Cardiazol, the hypoglycemic state raised insulin, psychotherapy and surgical intervention in the brain. Not develop here regarding the first and last.